2005
DOI: 10.1159/000081775
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus as a Risk Factor for Glaucomatous Optic Neuropathy

Abstract: Open-angle glaucoma (OAG) is an optic neuropathy characterized by progressive retinal ganglion cell (RGC) death and optic disk excavation. Evidence is accumulating that RGC apoptosis is the fundamental pathology of OAG. Among several risk factors for development and progression of OAG, inclusion of comorbid diabetes has been controversial. Some large population-based prevalence and incidence studies found a positive association between diabetes and OAG, whereas others did not. This inconsistency is derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 141 publications
2
59
0
2
Order By: Relevance
“…There is increasing evidence that diabetes causes microvascular damage and compromises glial and neuronal function and metabolism in the retina, making retinal neurons including retinal ganglion cells more susceptible to glaucomatous damage [4] . Additionally, diabetes seems to increase the susceptibility of retinal ganglion cells to stresses related to OAG such as elevated intraocular pressure (IOP) [5] .…”
mentioning
confidence: 99%
“…There is increasing evidence that diabetes causes microvascular damage and compromises glial and neuronal function and metabolism in the retina, making retinal neurons including retinal ganglion cells more susceptible to glaucomatous damage [4] . Additionally, diabetes seems to increase the susceptibility of retinal ganglion cells to stresses related to OAG such as elevated intraocular pressure (IOP) [5] .…”
mentioning
confidence: 99%
“…23 In addition to altering vascular tissues, DM compromises glial and neuronal functions and metabolism in the retina, which can make retinal neurons including retinal ganglion cells more susceptible to glaucomatous damage. 24 Furthermore, DM increases the susceptibility of retinal ganglion cells to additional stresses relating to OAG such as elevated IOP. 25 It seems reasonable to consider that a longer duration of DM with a prolonged insult to the retina and optic nerve via vascular, glial, and neuronal factors would be associated with a higher risk of OAG.…”
mentioning
confidence: 99%
“…3 Patients with diabetic retinopathy are at risk of developing glaucoma. 19 The measurement of visual field in eyes with glaucoma and coexisting diabetic retinopathy often is affected by retinal hemorrhage, exudates, and diabetesassociated retinal nerve fiber loss. 20 Previous studies have shown that MPC results in visual field defects in automated perimetry in a significant number of patients.…”
Section: Discussionmentioning
confidence: 99%